Simultaneous Assay of 14C and 3H in Evaporator Bottom by Chemical Oxidation Method - 안홍주; 이홍래; 한선호; Hong-Joo Ahn; Heung-Nae Lee; Sun-Ho Han (Journal of nuclear fuel cycle and waste technology (Online), 2005)
원전에서 발생된 농축폐액 방사성폐기물로부터 및 를 분리 정량하기 위하여 potassium persulfate와 sulfuric acid의 산화제를 이용하는 산화증류법을 적용하였으며, 와 는 각각 기체와 HTO 액체로 순차적으로 분리되었다. 분리된 와 는 액체섬광계수기를 이용하여 계수되었고, 소광효과를 보정하여 방사능을 측정하였다. 산화증류법을 검증하기 위하여 방사성 표준물은 와 , 그리고 의 3종류, 그리고 방사성 표준물은 HTO가 이용되었다. 또한 산화되기 어려운 방향족 화합물 중 을 대상으로 가장 최적의 산화 조건을 조사하고자 황산용액 농도에 따라 FT-IR 피크 변화를 평가하였다. 방사성표준시료의 경우와 동일한 방법으로 원전 농축폐액 시료로부터 와 를 분리 검출하였는데, 그 결과 회수율은 와 가 각각 Bq/g와 Bq/g로 검출되었다. [ ] and in the evaporator bottom (EB) discharged from the Nuclear power plant (NPP) were extracted simultaneously into a gaseous and liquefied HTO by using the chemical oxidation, which is the method to oxidize samples completely using potassium persulfate and sulfuric acid. The extracted and were counted by the liquid scintillation counter (LSC) after the quench correction. To examine the recovery of using the radioactive standards, , , and as , and HTO as were used. Also, the most suitable method for oxidizing , which is difficult to be oxidized, was investigated through FT-IR spectra according to the concentration of sulfuric acid. With the identical method, and in the EB generated in the NPP were assayed in the range of Bq/g and Bq/g, respectively.